Program Pembinaan Nilai Keislamanan Pada Akhlak Anak Usia Dini Di Desa Kandui - Wijaya, Supriadi; Saputra, Rendy; Eka Sari, Ema; Risdayanti, Risdayanti; Iqbal, Muhammad; Ummah, Nahdatul; Gofur, Abdul (Pamasa : Jurnal Pengabdian Pada Masyarakat, 2024)
This article is about the Islamic development program for children in Kandui Village, which includes teaching Quranic recitation at the Qur'anic Education Park (TPA), muhadharoh, Islamic Children's Festival (FAI), prayer practice and Islamic teaching at the madrasah. The main focus of this program is to instill morals and faith in children from an early age. Through Qur'an reading activities, religious discussions and teaching Islamic values, children are taught to understand and internalize religious teachings in their daily lives. This research identifies the positive impact of the program on children's character development, as well as the challenges faced in its implementation, including parental and community involvement. The results show that an integrated and collaborative approach can create an environment that supports the growth of faith and noble character in the younger generation in Kandui Village.